The Effect of the Money Supply on Inflation in ASEAN Region 5 Countries - Yohan*, Yohan; Sir, Samuel Y.; Cicilia, Vera Sri Endah; Armin, Armin (Universitas Syiah Kuala, 2023)
Inflation created in ASEAN 5 can be an economic problem amid economic pressure due to the COVID-19 pandemic. Changes in the money supply are expected to suppress inflation based on the belief that inflation is a monetary phenomenon, but this condition cannot be expected. Inflationary turmoil in ASEAN 5 countries has hurt the macroeconomy. The specific objectives of this study are to analyze the movement of the variables of Money Supply and Inflation in ASEAN 5 Region Countries and investigate the effect of Money Supply on Inflation in ASEAN 5 Region Countries. The analysis method used is panel data regression. Regression Panel data is divided into two, namely, balanced panel and unbalanced panel. Balanced data panels occur when each cross-section unit has the same number of time series observations. In contrast, unbalanced panel data occurs when each cross-section unit does not have the same number of time series observations. The test results show that the estimation results are based on the REM approach. The REM model shows intercept differences between ASEAN 5 countries, meaning that inflation rates in ASEAN 5 countries differ at different levels of the money supply. Therefore, research can be conducted based on the view that inflation is not only a monetary phenomenon but also comes from the demand-pull inflation side for cases in ASEAN 5 countries